2007
DOI: 10.1158/1078-0432.ccr-06-2383
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Heterozygosity of Chromosome 3 Detected with Single Nucleotide Polymorphisms Is Superior to Monosomy 3 for Predicting Metastasis in Uveal Melanoma

Abstract: Purpose: Loss of chromosome 3 is strongly associated with metastasis in uveal melanoma and has been proposed as the basis for clinical prognostic testing. It is not known whether techniques that identify loss of heterozygosity for chromosome 3 predict metastasis more accurately than those that detect only numerical loss of chromosome 3 (monosomy 3). Experimental Design: Fifty-three uveal melanomas were analyzed by 28 single nucleotide polymorphisms (SNP) across chromosome 3. SNP was compared with fluorescence … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 19 publications
5
86
0
Order By: Relevance
“…It has been reported that microRNA signatures differentiate melanoma subtypes; seven microRNAs (microRNA-142-3p, microRNA-486, m ic roR NA-214, m ic roR NA-218, m ic roR NA-362, microRNA-650 and microRNA-31) significantly correlated with acral melanoma compared to non-acral melanoma (15). Furthermore, let-7b and microRNA-199a were upregulated in uveal (ocular) melanoma, showing highly significant associations with the high metastatic gene expression signature and loss of chromosome 3, which have been shown to be more accurate predictors of metastasis than any clinical or pathological factors, and have served as surrogate endpoints for the identification of biomarkers in uveal melanoma (16)(17)(18). Similar findings have been found in both skin melanoma and uveal (ocular) melanoma, but it is unclear as to whether this finding is coincidental or whether it is an important indicator of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that microRNA signatures differentiate melanoma subtypes; seven microRNAs (microRNA-142-3p, microRNA-486, m ic roR NA-214, m ic roR NA-218, m ic roR NA-362, microRNA-650 and microRNA-31) significantly correlated with acral melanoma compared to non-acral melanoma (15). Furthermore, let-7b and microRNA-199a were upregulated in uveal (ocular) melanoma, showing highly significant associations with the high metastatic gene expression signature and loss of chromosome 3, which have been shown to be more accurate predictors of metastasis than any clinical or pathological factors, and have served as surrogate endpoints for the identification of biomarkers in uveal melanoma (16)(17)(18). Similar findings have been found in both skin melanoma and uveal (ocular) melanoma, but it is unclear as to whether this finding is coincidental or whether it is an important indicator of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal arms were scored as loss (mean log 2 ratio < -0.5), normal (-0.5 V mean log 2 ratio < 0.5), or gain (mean log 2 ratio z 0.5). These thresholds were previously established and validated (8,9). This analysis was expanded by the inclusion of 336 tumors from 13 publications (10 -22).…”
Section: Methodsmentioning
confidence: 99%
“…Array-based comparative genomic hybridization data were available from a previous study on 44 of the tumors listed in Supplementary Table S1 (6). Previously published samples were analyzed by either the Microarray Shared Resource at the Comprehensive Cancer Center, University of California-San Francisco, using a microarray-based platform containing a genome-wide collection of genomic contigs, or the Microarray and Genomics Facility of the Roswell Park Cancer Institute, using an array platform containing f6,000 BAC clones (5,11). For this study, both arms of each autosomal chromosome were scored for loss or gain based on log 2 mean raw ratio.…”
Section: Methodsmentioning
confidence: 99%